Transcription Factor Arabidopsis Activating Factor1 Integrates Carbon Starvation Responses with Trehalose Metabolism. Issue 1 (6th July 2015) - Garapati, Prashanth; Feil, Regina; Lunn, John Edward; Van Dijck, Patrick; Balazadeh, Salma; Mueller-Roeber, Bernd
Abstract : A transcription factor regulates trehalase expression and induces a carbon starvation transcriptome and metabolome. Abstract: Plants respond to low carbon supply by massive reprogramming of the transcriptome and metabolome. We show here that the carbon starvation-induced NAC (for NO APICAL MERISTEM/ARABIDOPSIS TRANSCRIPTION ACTIVATION FACTOR/CUP-SHAPED COTYLEDON) transcription factor Arabidopsis ( Arabidopsis thaliana ) Transcription Activation Factor1 ( ATAF1 ) plays an important role in this physiological process. We identified TREHALASE1, the only trehalase-encoding gene in Arabidopsis, as a direct downstream target of ATAF1. Overexpression of ATAF1 activates TREHALASE1 expression and leads to reduced trehalose-6-phosphate levels and a sugar starvation metabolome. In accordance with changes in expression of starch biosynthesis- and breakdown-related genes, starch levels are generally reduced in ATAF1 overexpressors but elevated in ataf1 knockout plants. At the global transcriptome level, genes affected by ATAF1 are broadly associated with energy and carbon starvation responses. Furthermore, transcriptional responses triggered by ATAF1 largely overlap with expression patterns observed in plants starved for carbon or energy supply. Collectively, our data highlight the existence of a positively acting feedforward loop between ATAF1 expression, which is induced by carbon starvation, and the depletion of cellular carbon/energy pools that is triggered by the transcriptional regulation of downstream gene regulatory networks by ATAF1.